Teachers' Perceptions on the Changes in the Curriculum and Exit Examinations for Biology and Human Biology - Kruger, Mirko; Won, Mihye; Treagust, David (Social Science Press, 2013)
In the age of educational accountability, national and state-wide measures are assumed to secure and improve the educational quality. However, educators often wonder how much a new accountability measure may improve the actual teaching and learning practices when the agents of change (teachers) are not active participants of such educational reform. Nevertheless, in Australia, the National Curriculum is rolling in for the first time for K-10 school education in 2012-13. In Western Australia, the new Western Australian Certificate of Education (WACE) system with new compulsory exit examination requirements has been implemented recently for Years 11-12. In this study, using the contextual curriculum theory (Cornbleth, 1990) and the levels of curriculum (van den Akker, 1998, 2003) as our theoretical framework, we investigated how experienced Biology teachers are making sense of the recent changes in the curriculum and the exit examination requirements: what they perceive as the major changes in the new WACE system; and how they implement the changes in their teaching practice. We discuss how the teachers’ teaching philosophy, their school environments, and the new curriculum interact to create a spectrum of the implemented curriculum.